Estética na velhice: a percepção da mulher idosa - Mello, Márcia de (2019)
Following a worldwide trend, Brazil lives a new socio-demographic reality, with dizzying grow rates of the elderly population. The increase in life expectancy, one of the greatest achievements mankind, brought new challenges in face of old age. Among them, the search for a healthy, ac and emancipated aging, contradictory ideal, in contemporary society that treats the body as capi worshiping beauty and youthfulness as the dominant social model. The present study aimed to kn the perception of the elderly about their body aesthetics and how this understanding can influence sense of self-efficacy in daily life. To achieve this purpose, a qualitative, exploratory and descript research was conducted in a coexistence group, linked to a university extension program in the inte of the state of Rio Grande do Sul. Eleven women aged 60 to 80 were interviewed. years, fr November to December 2018. The information obtained was analyzed following the thematic con analysis technique, which allowed the construction of two categories: feeling good is the keywo care with appearance. The results are presented in Scientific Production I, entitled “Perception body aesthetics of older women in a social group”, which showed that appearance is perceived as important aspect to feel good about yourself and others, confident and happy. However, it does occupy a prominent place in daily life. The care that the elderly women in this study expressed hav showed the understanding of the association between health and beauty. Scientific Production entitled “Aesthetics and the sense of self-efficacy in aging” aims to reflect how body aesthe contributes to the individual's self-efficacy in the aging process. The results point to the importa of a new look and meaning to the aesthetic values of health and life, in order to contribute to a posit self-concept and a greater sense of self-efficacy.